National hero expose 9/11 cover up! - Rodriguez, William; Saba Islamic Media ([Kuala Lumpur] : Saba Islamic Media [distributor])
A talk by William Rodriguez, the last survivor of the twin tower that exposes on what the media failed to tell you
Title from container
Speaker: William Rodriguez
Keywords: September 11 Terrorist Attacks, .; Terrorism -- United States